2018
DOI: 10.1016/j.ejrad.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance T1 mapping. Part 2: Diagnostic potential and applications

Abstract: Non-invasive identification and differentiation of myocardial diseases represents the primary objectives of cardiac magnetic resonance (CMR) longitudinal relaxation time (T1) and extracellular volume (ECV) mapping. Given the fact that myocardial T1 and ECV values overlap throughout and within left ventricular phenotypes, a central issue to be addressed is whether and to what extent myocardial T1 and ECV mapping provides additional or superior diagnostic information to standard CMR imaging, and whether native T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 100 publications
0
31
0
4
Order By: Relevance
“…The detection of chemotherapy cardiotoxicity has already been proposed among the possible clinical uses of ECV (35). Indeed, Jordan et al (36) and Neilan et al (37), have assessed ECV as a biomarker of anthracycline cardiotoxicity using CMR T1-mapping before/after the administration of gadolinium-based contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of chemotherapy cardiotoxicity has already been proposed among the possible clinical uses of ECV (35). Indeed, Jordan et al (36) and Neilan et al (37), have assessed ECV as a biomarker of anthracycline cardiotoxicity using CMR T1-mapping before/after the administration of gadolinium-based contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, native T1 mapping was found to be an effective test for differentiating between controls and DCM with good diagnostic accuracy, specificity, and NPV, but not for sensitivity and PPV. The possible reason for limited sensitivity and PPV may be related to the accuracy of co-registration of thin-wall myocardium in DCM cases that is subjected to a potential measurement errors [ 29 ]. For differentiating HCM from controls, the average native T1 was found to have good diagnostic accuracy, specificity, and NPV, but it has limited sensitivity and PPV.…”
Section: Discussionmentioning
confidence: 99%
“… 58‐60 Image quality was visually good. For the patient with suspected HHD, increased T1 and T2 was observed in the septal region and patchy structures in the T1 map as typically observed in HHD 61 . No reference methods were acquired in patients, which will be evaluated in future work.…”
Section: Discussionmentioning
confidence: 99%